2013
DOI: 10.1021/nn3051264
|View full text |Cite
|
Sign up to set email alerts
|

Directed Assembly of High Molecular Weight Block Copolymers: Highly Ordered Line Patterns of Perpendicularly Oriented Lamellae with Large Periods

Abstract: The directed assembly of block copolymer nanostructures with large periods exceeding 100 nm remains challenging because the translational ordering of long-chained block copolymer is hindered by its very low chain mobility. Using a solvent-vapor annealing process with a neutral solvent, which was sequentially combined with a thermal annealing process, we demonstrate the rapid evolution of a perpendicularly oriented lamellar morphology in high molecular weight block copolymer films on neutral substrate. The syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 54 publications
(78 reference statements)
1
141
0
Order By: Relevance
“…To the best of our knowledge, the longest pitch of a nano-pattern formed with BCP was around 200 nm [8]. In contrast, we were able to obtain nano-patterns larger than 200nm by using a BCP whose molecular weight was over 1 million.…”
Section: Resultsmentioning
confidence: 78%
“…To the best of our knowledge, the longest pitch of a nano-pattern formed with BCP was around 200 nm [8]. In contrast, we were able to obtain nano-patterns larger than 200nm by using a BCP whose molecular weight was over 1 million.…”
Section: Resultsmentioning
confidence: 78%
“…This method has already been reported in previous studies regarding DSA defects. [ 32,35 ] For line/space patterns, typical examples of self-assembly defects are dots, junctions, dislocations, and terminal points. According to a power law, the defect density ( ρ ) of self-assembled BCP patterns as a function of the assembly time ( t ) can be expressed as t v ρ − , where v is the empirical kinetic exponent.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30,34 ] Ryu et al found that two-step annealing consisting of solvent and thermal treatments is highly effective for the assembly of high-N BCPs. [ 35 ] Ross and co-workers also reported a signifi cant reduction of the assembly time of BCPs on densely guided narrow trench templates by rapidly increasing the substrate temperature following a conventional room-temperature solvent annealing process. [ 36 ] However, the rapid, one-step assembly of long-range ordering of high-χN BCPs on micrometer-scale wide templates, obtainable by low-cost photolithography, has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports on large BCP features are now evident and may present an ideal route to fabricating metamaterials and photo nic structures. [ 220 ] Reports have detailed the self-assembly of large periods using large molecular weight (>1 million g mol −1 ) BCPs [ 221 ] and brush-type BCPs. [ 222,223 ] A recent review [ 224 ] has also highlighted this emerging area of patterning large period features from such polymer materials.…”
Section: Extending Incorporation Methods To Ultra-low Bcp Nanodimensionsmentioning
confidence: 99%